A new real‐time cycle slip detection and repair approach based on BDS dual‐frequency carrier phase and Doppler observations. Issue 1 (11th August 2021) - Shi, Zengkai; Dong, Xurong; Qian, Zhaoyong; Sun, Xiaoshuang; Hu, Yanfeng
Abstract: The Global Navigation Satellite System (GNSS) traditional dual‐frequency cycle slip detection and repair methods such as the TurboEdit algorithm are restricted by the availability and accuracy of pseudorange observations. Doppler observations represent the instantaneous variation of the carrier phase during the integration time, which are immune to cycle slips. They are less affected by multipath effects compared with the pseudorange observations. Hence, a real‐time cycle slip detection and repair approach for the BeiDou Navigation Satellite System (BDS) dual‐frequency signals is proposed by combining the carrier phase and Doppler observations. The proposed method adopts the phase‐Doppler combination and the geometry‐free combination to detect cycle slips, and uses the simple rounding method or the dual‐frequency least‐square ambiguity decorrelation adjustment (LAMBDA) method to repair cycle slips. The validity of the proposed method is verified by the static and kinematic observation data under 1 s sampling interval and steady ionosphere. The results show that the new method can successfully detect all the small, insensitive, and large cycle slips. Moreover, the fixing rates of the simple rounding method under static and kinematic conditions are above 94% and 83%, respectively, while those of the dual‐frequency LAMBDA method are both 100%.